Development of a falls reduction yoga program for older adults—A pilot study. (April 2017) - Smith, Paul D.; Mross, Paul; Christopher, Nate
Abstract: Objectives: Work with local rural organizations to develop an evidence-based hatha yoga program intended to improve core strength and balance to reduce falls risk. Feasibility determined by successful recruiting, intervention and evaluation of participants and acceptable frequency of adverse events. Design: Single-arm pilot study. Setting: Rural Wisconsin town of 4200 people. Intervention: Eight week yoga program with weekly group classes and home yoga practice three times per week. Main outcome measures: The primary outcomes were (1) ability to enroll at least 20 participants, (2) participant completion of intervention and post-intervention evaluation, and (3) adverse event description and frequency. Results: A convenience sample of 20 adults over age 59 was enrolled and started the program with one drop out. Participants attended a mean of 7.1 (SD 1.47) of the 8 classes and a total of 141 out of 160 (88.1%) classes. Nineteen (95%) completed follow up evaluation. Participants reported 4 falls in the month before the intervention and 1 fall the month before the post-intervention evaluation (p = 0.34). No other serious adverse events occurred. Conclusions: This project suggests an evidence-based yoga program designed to improve core strength and balance is feasible and acceptable to participants. Future research will include a randomized trial to assess impact on falls risk.